Why. - World Hunger Year. (New York, N.Y. : WHY (World Hunger Year), 1989)
"Challenging hunger and poverty."
Title from cover.
From 2000 published on internet only: www.worldhungeryear.org
Some issues combined.
Keywords: Poor -- Periodicals; Malnutrition -- Periodicals; Hunger -- Periodicals; Food supply -- Periodicals